Media and National Development in Democratic Societies - Suleiman M. Yar’Adua; Aondover Eric Msughter; Sabiu Garba (Polit Journal Scientific Journal of Politics, 2023)
The operation of the media in terms of national development is fundamental for the productivity of any journalistic engagement. The objective of development communication entails the media carrying out development tasks within the context of the society as well as advocating the essence why society should develop. This is paramount because development is a process that should target individuals and groups and by extension the society at large and should aim towards improving the quality of all aspects of people’s lives, ranging from the economic, the political, the socio-cultural and even the technological. In this direction, this paper examines media and national development, development communication and development reporting, the imperativeness of development news reporting, and the role of the media in fostering development. The paper adopted the theoretical tenets of Development Media Theory, and Agenda-setting Theory to interrogate media and national development. The secondary source of data was employed using journal articles, textbooks and the internet. The paper argued that the media played a double-edged role which may either enhance or derail national development. The paper concludes that the objective of development communication entails the media carrying out development tasks as well as advocating the essence why society should develop. The paper recommends that the media should be socially responsible in carryout development tasks that will foster national development, and such developmental goals should be based on a button-to-top approach.